1997
DOI: 10.1007/bf00434114
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spinal cord compression in hereditary multiple exostoses

Abstract: Spinal cord compression is an extremely serious complication of hereditary multiple exostoses (HME). A case of HME with compression of the cervical spinal cord is reported. Complete recovery following surgery was achieved. A review of the relevant literature revealed 51 previous cases of HME with cord/cauda equina compression. Most patients were under 30 years of age with more men affected than women. The family history was positive in 60%. The cervical and thoracic areas were predominantly affected, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The family history is positive in approximately 60%, with autosomal dominant inheritance 5 . The exostoses usually involve long bones, and they seldom occur in the axial skeleton, occurring in only 7–9% of patients with HME 1,3–6 . The exostoses grow slowly during childhood and adolescence and growth ceases with skeletal maturation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The family history is positive in approximately 60%, with autosomal dominant inheritance 5 . The exostoses usually involve long bones, and they seldom occur in the axial skeleton, occurring in only 7–9% of patients with HME 1,3–6 . The exostoses grow slowly during childhood and adolescence and growth ceases with skeletal maturation.…”
Section: Discussionmentioning
confidence: 99%
“…However, spinal cord compression resulting from osteochondroma is an extremely serious and unusual complication of HME. Possible symptoms resulting from compression include myelopathy, paraplegia, paraesthesia, paresis and radiculopathy 3–10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reported cases involved the cervical and thoracic region, and the majority presented with symptoms suggestive of a slowly growing spinal cord tumor. 5,12,18 In a review of the literature available in 1951, Slepian and Hamby 13 found only 21 reported cases of neurologic complications in over 1000 cases. We believe that predilection of the involvement site may be related to the low incidence of neuropathy in patients with osteochondroma.…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondromas rarely affect the spine; 1.3% to 4.1% of solitary osteochondromas arise within the spine, and approximately 9% of patients with multiple osteochondromas have spinal lesions. [3][4][5] Understanding embryological development of spine could also conjecture on other etiological hypothesis. The complete growth of the vertebral column is completed in adolescence by secondary ossification centers at the spinous process, transverse process, articular process, and end plate of vertebral body.…”
Section: Discussionmentioning
confidence: 99%